The Surprising Retreat of Union Britain - John H. Pencavel (Institute for the Study of Labor (IZA), 2003)
After expanding in the 1970s, unionism in Britain contracted substantially over the next two decades. This paper argues that the statutory reforms in the 1980s and 1990s were of less consequence in accounting for the decline of unionism than the withdrawal of the state?s indirect support for collective bargaining. The principal goal of the reforms was to boost productivity so the paper examines the link between unions and productivity finding only a small association by the end of the 1990s. Private sector unionism has become highly decentralized which renders it vulnerable to the vagaries of market forces.
Keywords: J5; 330; unions; Britain; Gewerkschaftlicher Organisationsgrad; Gewerkschaft; Gewerkschaftspolitik; Tarifpolitik; Produktivität; Großbritannien